Formulation analyses of high-volume prescription drugs. Issue 2 (June 2019) - Fawcett, T.G.; Gates-Rector, S.; Gindhart, A.M.; Rost, M.; Kabekkodu, S.N.; Blanton, J. R.; Blanton, T. N.
Abstract : A collection of 65 formulated tablets and capsules were analyzed for phase composition by full pattern matching powder diffraction methods. The collection contained 32 of the top 200 prescription drugs sold in 2016 as well as many high-volume prescriptions and over the counter drugs from prior years. The study was used to evaluate new methods of analysis as well as the efficacy of programs designed to collect references on high volume excipients and pharmaceuticals for inclusion in the Powder Diffraction File ™ . The use of full pattern matching methods as well as reference pattern additions of many common excipients enabled major phase excipient identification in all formulations. This included identification of crystalline, nanocrystalline, and amorphous ingredients because full pattern matching involved the use of characteristic coherent and incoherent scatter. Oftentimes identification of the major excipients significantly aided the clean identification of the active pharmaceutical ingredients (APIs) and their polymorphic form, even at low concentrations (1–10 wt. %). Overall 93% of the APIs were identified, most through a PDF ® material reference, but also through patent cross-referencing and similarity analysis comparisons.